Randomised controlled trial of high concentration versus titrated oxygen therapy in severe exacerbations of asthma. Issue 11 (19th May 2011) - Perrin, Kyle; Wijesinghe, Meme; Healy, Bridget; Wadsworth, Kirsten; Bowditch, Richard; Bibby, Susan; Baker, Tanya; Weatherall, Mark; Beasley, Richard
Abstract : Background: The effect on Paco 2 of high concentration oxygen therapy when administered to patients with severe exacerbations of asthma is uncertain. Methods: 106 patients with severe exacerbations of asthma presenting to the Emergency Department were randomised to high concentration oxygen (8 l/min via medium concentration mask) or titrated oxygen (to achieve oxygen saturations between 93% and 95%) for 60 min. Patients with chronic obstructive pulmonary disease or disorders associated with hypercapnic respiratory failure were excluded. The transcutaneous partial pressure of carbon dioxide (Ptco 2 ) was measured at 0, 20, 40 and 60 min. The primary outcome variable was the proportion of patients with a rise in Ptco 2 ≥4 mm Hg at 60 min. Results: The proportion of patients with a rise in Ptco 2 ≥4 mm Hg at 60 min was significantly higher in the high concentration oxygen group, 22/50 (44%) vs 10/53 (19%), RR 2.3 (95% CI 1.2 to 4.4, p<0.006). The high concentration group had a higher proportion of patients with a rise in Ptco 2 ≥8 mm Hg, 11/50 (22%) vs 3/53 (6%), RR 3.9 (95% CI 1.2 to 13.1, p=0.016). All 10 patients with a final Ptco 2 ≥45 mm Hg received high concentration oxygen therapy, and in five there was an increase in Ptco 2 ≥10 mm Hg. Conclusion: High concentration oxygen therapy causes a clinically significant increase in Ptco 2 in patients presenting with severe exacerbations of asthma. A titrated oxygen regime is recommended in the treatment of severe asthma, in which oxygen is administered only to patients with hypoxaemia, in a dose that relieves hypoxaemia without causing hyperoxaemia. Clinical trial number: ACTRN12607000131459.